Examining the Efficacy of Title VI Social Equity Analysis: A Comparative Case Study of Transit Access and Neighborhood Segregation Outcomes Over Time. (4th July 2018) - Larson, Samantha June
Abstract : An overarching question concerns why social inequity persists despite decades of policy intervention. For instance, Title VI of the Civil Rights Act of 1964 mandated that agencies must not discriminate based on race, ethnicity, or national origin to receive federal funding. Transportation agencies were particularly impacted. They have since submitted equity analyses for every bus and rail expansion and/or reduction to verify they do not disproportionately impact minority and low-income communities. This study moves beyond a momentary analysis to examine the extent to which transit development has impacted communities of color from 1970–2010. Income segregation outcomes are examined in neighborhoods across four diverse metropolitan areas: Denver, Minneapolis, Birmingham, and Orlando. A fixed effects regression analysis illustrates mixed results. This study concludes by discussing what fairness looks like in neighborhoods when taking race and ethnicity into account. It suggests further consideration of Title VI as a tool to hold administrators accountable for social equity beyond single points in time.